A comparative study of ebay and amazon electronic commerce platforms - Yousef A. Baker, El-Ebiary; Hasni, Hassan; Julaily Aida, Jusoh; Ahmad Nazari, Mohd Rose; Syarilla Iryani, Ahmad Saany; Waheed Ali H. M., Ghanem (2021)
The key target of this documentation is to study and compare e-commerce platforms between e-Bay and Amazon. While Amazon.com gained more promotions and underlying exposure to web-based businesses, eBay has secretly built inventories that are truly Internet-friendly. The research used an analytical method to find the difference between these two platforms. Initially, Amazon was only trying to reproduce a list of action plans on the web. The innovation may be inventive, but the design of the action is certainly not. Once again, eBay has a great idea of the Internet network and has empowered supply and demand on the web with incredible outcomes. The sales position is the winner. Besides, eBay clearly shows that the benefits do not need to be in the idea of development - a dispute that Bezos never made. Amazon initially centered around BN.com as a competitor. After a while, Amazon saw eBay as a competitor. The underlying attack was a tremendous disappointment. Currently, Amazon is endeavoring to contend with eBay by driving sales and consolidating its partner programs.